KOMPOSISI JENIS BIOFOULING PADA TIRAM MUTIARA (PINCTADA MAXIMA) DI LAHAN BUDIDAYA PT. AUTORE PEARL CULTURE LOMBOK - Jefri, Edwin; Yasir, Inayah; Syafiuddin, Syafiuddin (Hasanuddin University, 2017)
Cultivation of pearl oyster Pinctada maxima types are increasingly in demand in Indonesia. This oyster living and concentrated on waters that have coral reefs and sandy rubble. Oyster cultivation is very promising given pearls produced have a high economic value. Eventhough, pearl oyster farming efforts not always performing well because there is a possibility of oysters will get the disease and even death. One reason is their biofouling attached to the basket or on the oyster shell is maintained. The existence and amount of biofouling usually varies depending on the time and conditions of the waters where the cultivation have been. This study aims to determine the types of biofouling were found at three different sites located on land cultivation PT. Pearl Culture Autrore Lombok. Study sample is limited to biofouling found on new and used baskets and pearl oyster shells P. maxima. The main parameters measured were the species composition and abundance, while the supporters of the parameters measured were temperature, salinity, current speed, the brightness of the waters and TSS (Total Suspended Solid). The results found 36 types of biofouling, including 21 types of animal groups with six phyla (arthropods, bryozoans, annelids, cnidarians, sponges and molluscs), and 15 species of the plant with two divisio (Spermatophyta and Thallophyta). In addition, it was found that water conditions have an influence on the biomass and the number of types of biofouling and the distance between substations in each station does not have a significant influence on biomass and the number of types of biofouling.Keywords: Biofouling, Pearl Oyster (Pinctada maxima ), PT. Autore Pearl Culture Lombok